A NOVA CONFIGURAÇÃO DA POLÍTICA DE SAÚDE NO BRASIL: o Rio de Janeiro como laboratório - Débora Holanda Leite Menezes (Universidade Federal do Maranhão, 2016)
This text discusses the changes in the management of public health services in Brazil since 1990. It aims to analyze how, over the last 30 years, these services lose their public and universal character, assuming a privatized nature. The methodology includes a literature review and a study on the functioning of the public healthcare system of Rio de Janeiro - privileged locus because of the number of health facilities, and the rapid accession of their rulers to new management models. It concludes that the biggest losses of the adoption of these models will fall on the poor, who depend on public health services. Furthermore, the precarious working conditions and salaries of health professionals also comes on way to a model that ignores the value of life and health, since this common good is just another commodity. Who does not pay, do not have.